Defects in DNA double‐strand break repair resensitize antibiotic‐resistant Escherichia coli to multiple bactericidal antibiotics - Sarah A. Revitt‐Mills; Elizabeth K. Wright; Madaline Vereker; Callum O'Flaherty; Fairley McPherson; Catherine Dawson; Antoine M. vanOijen; Andrew Robinson (MicrobiologyOpen, 2022)
Abstract Antibiotic resistance is becoming increasingly prevalent amongst bacterial pathogens and there is an urgent need to develop new types of antibiotics with novel modes of action. One promising strategy is to develop resistance‐breaker compounds, which inhibit resistance mechanisms and thus resensitize bacteria to existing antibiotics. In the current study, we identify bacterial DNA double‐strand break repair as a promising target for the development of resistance‐breaking co‐therapies. We examined genetic variants of Escherichia coli that combined antibiotic‐resistance determinants with DNA repair defects. We observed that defects in the double‐strand break repair pathway led to significant resensitization toward five bactericidal antibiotics representing different functional classes. Effects ranged from partial to full resensitization. For ciprofloxacin and nitrofurantoin, sensitization manifested as a reduction in the minimum inhibitory concentration. For kanamycin and trimethoprim, sensitivity manifested through increased rates of killing at high antibiotic concentrations. For ampicillin, repair defects dramatically reduced antibiotic tolerance. Ciprofloxacin, nitrofurantoin, and trimethoprim induce the promutagenic SOS response. Disruption of double‐strand break repair strongly dampened the induction of SOS by these antibiotics. Our findings suggest that if break‐repair inhibitors can be developed they could resensitize antibiotic‐resistant bacteria to multiple classes of existing antibiotics and may suppress the development of de novo antibiotic‐resistance mutations.